The effect of clinician-expressed empathy and nocebo-alleviating information on breast-cancer-patients' anxiety and side effects during active chemotherapy: A clinical feasibility study - Lara C. Gröschel; Fiona T. Brosig; Marcel Soesan; Katherina T. Vourtsis; Mirte van der Spek; Elise Sluiter; Liesbeth M. van Vliet (PEC Innovation)
Objective: We set up a pilot-study to investigate main and interaction effects of nocebo-alleviating information and clinician-expressed empathy delivered via a standardized information-video on breast cancer patients' psychological and side effect outcomes during chemotherapy. Additionally, we aimed to reflect on the feasibility of the intervention (acceptability, practicality and integration) to inform future – follow-up – studies. Methods: Using a clinical proof-of-principle randomized controlled trial, female breast cancer patients undergoing chemotherapy viewed one of four videos, varying in the level of nocebo-alleviating information(+/−) and clinician-expressed empathy(+/−). Due to the small sample size (n = 27), descriptive and recruitment data were utilized to evaluate effects and reflect on feasibility. Results: The interventions appeared to yield limited effects on our small sample. Feasibility reflections mainly focused on the practical level, such as the use of more generalizable videos and optimizing the flow. Conclusion: The study showed limited effects of the video intervention. It revealed recruitment challenges, while acceptability was high after inclusion. Moving forward, face-to-face clinician-patient interactions remain important, while cautiously exploring the potential benefits of modern technological advancements, ensuring thorough testing of their effects before implementation. Innovation: This study marks an innovative approach in utilizing digital interventions to enhance cancer patient outcomes within clinical settings.